Constitutionalism and the economy in Africa - Fombad, Charles Manga; Steytler, N. C. (Oxford : Oxford University Press, 2022)
This edited volume looks at the relationship between constitutional law and the African political economy. It tackles a range of issues from the impact of globalization to the State's role in the economy, and the constitutional foundations for land and natural resources exploitation, regulation and protection.
This edition also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 19, 2022).
Keywords: Africa -- Economic conditions -- 21st century; Africa -- Politics and government -- 1960-; Constitutional law -- Africa; Industry; Industry & industrial studies